Métricas de avaliação de eficiência de plantas fotovoltaicas - Yamada, Guilherme Dan (2021)
To ensure the return on investment of a grid connected photovoltaic plant, over its lifetime of five years or more, monitoring and guaranteeing its operation efficiency is required. Even though there is no single metric that provides the global efficiency of a photovoltaic plant, it is possible to monitor the plant operational quality by means of a varied set of metrics, referenced on the standards of the area and on technical and scientific publications. This master of science research conducted a study over performance metrics and selected a set of eight metrics to perform the efficiency analysis of photovoltaic plants. Additionally, an Efficacy metric was proposed aiming towards evaluating the relation between a photovoltaic plant’s produced energy and its expected energy generation. A case study was developed on a UTFPR’s 5kWp photovoltaic plant, aiming to apply the proposed metrics for efficiency analysis. The obtained results from a one-hundred and fifty-days sampling period are presented, allowing one to observe the behavior and the interrelations between the considered metrics, enlarging this analysis compared to those commonly found in the literature.